2015
DOI: 10.1080/10601325.2015.1050638
|View full text |Cite
|
Sign up to set email alerts
|

Polyblend Nanocomposites

Abstract: Blending polymers is used to obtain products with improved and wider range of properties. A polymer blend or polyblend is a microscopically mixture of two or more polymers. This paper deals with polyblend nanocomposites where one of the components has at least one dimension of the order of nanometer. It covers different groups of nanocomposites depending on the type of the polymer used in such mixtures, mainly:thermoplastic -thermoplastic polymer blend nanocomposites, thermoplastic -thermoset polymer blend nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…Intensive research efforts are also dedicated to the synthesis of self-healing thermoset polymers by including organic/inorganic nanofillers during in-situ polymerization to improve the nanofiller distribution, strength, modulus, and toughness of the final thermoset nanocomposite material to achieve further improvements [14,15,16,17]. As a normal procedure, the weight content of the nanofiller (e.g., carbon nanotubes) in the matrix is tailored to gain the maximal reinforcement from the filler while considering its aspect ratio and loading.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive research efforts are also dedicated to the synthesis of self-healing thermoset polymers by including organic/inorganic nanofillers during in-situ polymerization to improve the nanofiller distribution, strength, modulus, and toughness of the final thermoset nanocomposite material to achieve further improvements [14,15,16,17]. As a normal procedure, the weight content of the nanofiller (e.g., carbon nanotubes) in the matrix is tailored to gain the maximal reinforcement from the filler while considering its aspect ratio and loading.…”
Section: Introductionmentioning
confidence: 99%
“…A key method for tuning the optical properties of SPNs is by preparing polymer blends prior to nanoparticle formation, resulting in what can be referred to as polyblend SPNs. 10 Several studies reported the synthesis of polyblend SPNs from a blend of two conjugated polymers; 11,12 Huebner et al 12 reported the synthesis of PFO:POPPV SPNs from a blend of a blue emitting (PFO) and a green emitting (POPPV) polymer. The blending resulted in a material with controllable photoemission caused by the tunable energy transfer within the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, blending two or more polymers is an easy way to obtain new products with improved and wider properties and applications. On the other hand, the nanoscience has opened a new opportunity to use the polyblend as a matrix for loading some nanoscaled particles, where the incorporation of a small amount of the nano‐sized material can change the physiochemical properties of the blend significantly . Carboxymethyl cellulose (CMC) is an abundant polysaccharide, biodegradable, biocompatible, linear, and water‐soluble biopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the nanoscience has opened a new opportunity to use the polyblend as a matrix for loading some nanoscaled particles, where the incorporation of a small amount of the nano-sized material can change the physiochemical properties of the blend significantly. [1][2][3][4] Carboxymethyl cellulose (CMC) is an abundant polysaccharide, biodegradable, biocompatible, linear, and water-soluble biopolymer. CMC is used in the cosmetics industries, as an emulsion stabilizer and a carrier of functional materials.…”
Section: Introductionmentioning
confidence: 99%